(untitled) (Bangladesh Journal of Neuroscience, 2017)
Background: Stroke is the third leading cause of death in adult population throughout the world and is the most common cause of severe adult physical disability. It is increasing at an alarming rate in Asia including Bangladesh. The effect of recurrent stroke is devastating on patient as it is the main reason of mortality and morbidity among patients. Methods: A longitudinal, observational study was conducted from April 2018 to October 2018 in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. All the patients of first ever ischemic stroke confirmed by neuroimaging (CT scan of head / MRI of brain), meeting the inclusion and exclusion criteria were included in the study. Our study was performed with sixty stroke patients. We followed up patient up to 90 days and observed for stroke recurrence. Results: Present study showed among the 60 stroke patients, only 4 (6.67%) suffered from stroke recurrence within 3 months. In our study, uncontrolled systolic blood pressure (p=0.04), uncontrolled diastolic blood pressure (p=0.027), dyslipidaemia (p=0.001), smoking (p=0.0003) and antiplatelet discontinuation (p=0.0001) were significantly associated with stroke recurrence whereas uncontrolled diabetes mellitus (p=0.46) and presence of atrial fibrillation (p=0.057) had no significant association. Conclusion: Smoking, hypercholesterolemia, uncontrolled systolic &/or diastolic blood pressure and discontinuation of antiplatelet therapy were significantly associated with stroke recurrence in this population. Therefore, early identification and control of these risk factors are essential to prevent recurrent stroke, thereby decrease morbidity and mortality. Bangladesh Journal of Neuroscience 2017; Vol. 33 (2): 55-62